HUBUNGAN PENGETAHUAN PERSONAL HYGIENE DAN PERILAKU SAAT MENSTRUASI PADA REMAJA PUTRI DI SEKTOR TALITAKUMI 1 DESA WAAI KABUPATEN MALUKU TENGAH - Nanlohy, Wildia; Wakano, Melawati; Salmon, Kristy Hetreda; Thalib, Abdul (STIKES Pasapua Ambon, 2022)
Introduction: Adolescence is a dynamic developmental phase in one’s life. Where this period is a transition from childhood to adulthood which is characterized by developments ranging from physical, mental, emotional, and social. The general objective is to find out the relationship between personal hygiene knowledge and behavior during menstruation in young women in the Talita Kumi 1 sector, Waai Village, Central Maluku Regency. Method: The research method used was an analytical survey, with a cross-sectional study design. Sampling used a total sampling technique with a total of 38 respondent. Results: The results obtained were that 13 respondents (34.2%) had good knowledge in the talitakumi sector 1, while 25 respondents (65.8%) had poor knowledge. Adolescents with good behavior were 26 respondents (68.4%), while adolescents with unfavorable behavior were 12 respondents (31.6%). The relationship between knowledge and adolescent behavior during menstruation in the talitakumi1 sector in Waai village was a statistical test at p = 0.064, in other words the p-value in this study was greater than 0.05. Conclusion: There was no relationship between knowledge and adolescent behavior during menstruation.